Analisa Kuat Tekan Beton Akibat Pengaruh Penggunaan Limbah Batu Bata - Okky Hendra Hermawan; Muhamad Fajar Sidiq; Nadya Safira; Aulia Rahman (Universitas Teuku Umar, 2021)
Concrete is a building material consisting of a mixture of cement, water, fine aggregate, coarse aggregate in a certain ratio. With the number of buildings that use concrete, the demand for concrete increases, and the use of aggregate as a supporting material for concrete increases as well. Innovation in concrete-forming materials can be done by substituting substitute materials, either aggregates or other materials by utilizing the waste that is around us. One of the wastes that can be used around us is brick waste. From the above phenomenon, the researcher will innovate on the concrete constituent materials by utilizing waste bricks as a substitute for fine aggregate to find out how much the compressive strength of concrete is at the age of 7 days and 28 days. The effect of adding brick powder to the concrete mixture resulted in a decrease in the compressive strength of the concrete. The higher the percentage of brick powder added to the concrete mixture, the lower the compressive strength of the concrete will be